PENGARUH LINGKUNGAN KERJA, KEPEMIMPINAN, MOTIVASI KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KEPUASAN KERJA PEGAWAI (Studi Pada Dinas Kehutanan Jawa Tengah) (Students' Journal of Economic and Management, 2014)
Research on the influence of the work environment, leadership, work motivation and organizational commitment on job satisfaction (Studies in Central Java Forestry Office), take the 53 respondents with a significance level of 5%, the data used primary data, data analysis using quantitative analysis include test validity, reliability test, multiple regression analysis, t test, F test and the coefficient of determination.Based on the data analysis can be concluded as follows: Leadership highest positive effect on job satisfaction employee means good leadership can be done by a leader lends support to subordinates in order to carry out tasks without being weighed down. The second positive effect of organizational commitment on job satisfaction means employee organizational commitment can either be done by giving direction to subordinates to accept any job duties of the agency. Work motivation third positive effect on job satisfaction means employee motivation needs to be given to an employee can be done by the leadership must give direction to subordinates that everything can be achieved through hard work. The work environment has a positive effect on job satisfaction lowest employee work environment means that must be achieved is by way of leadership must know the equipment in accordance with standard work already working.Keywords: Work Environment, Leadership, Motivation, Organizational Commitment and Job Satisfaction